2012
DOI: 10.1111/j.1365-3180.2012.00926.x
|View full text |Cite
|
Sign up to set email alerts
|

Alien aquatic plant species in European countries

Abstract: Hussner A (2012). Alien aquatic plant species in European countries. Weed Research52, 297–306. Summary Alien aquatic plant species cause serious ecological and economic impacts to European freshwater ecosystems. This study presents a comprehensive overview of all alien aquatic plants in Europe, their places of origin and their distribution within the 46 European countries. In total, 96 aquatic species from 30 families have been reported as aliens from at least one European country. Most alien aquatic plants ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
135
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(150 citation statements)
references
References 34 publications
0
135
0
4
Order By: Relevance
“…Other human impacts that affect carbon and nitrogen cycling in river networks that can potentially influence cycling of GHGs are river bank stabilization and floodplain drainage that disrupt the river-wetland connectivity that is important for CO 2 and CH 4 dynamics in rivers (Abril et al, 2014;Teodoru et al, 2015;Borges et al, 2015aBorges et al, , 2015bSieczko et al, 2016). The introduction of invasive animal species such as the zebra mussel (Dreissena polymorpha) in US rivers and lakes (Caraco et al, 1997;Evans et al, 2011) (Hussner, 2012), some with high production and biomass (Hussner, 2009); invasive floating macrophytes such as the water hyacinth (Eichhornia crassipes) have been documented to increase CO 2 and CH 4 levels in tropical rivers (Koné et al, 2009(Koné et al, , 2010, but this remains undocumented in temperate rivers.…”
Section: Introductionmentioning
confidence: 99%
“…Other human impacts that affect carbon and nitrogen cycling in river networks that can potentially influence cycling of GHGs are river bank stabilization and floodplain drainage that disrupt the river-wetland connectivity that is important for CO 2 and CH 4 dynamics in rivers (Abril et al, 2014;Teodoru et al, 2015;Borges et al, 2015aBorges et al, , 2015bSieczko et al, 2016). The introduction of invasive animal species such as the zebra mussel (Dreissena polymorpha) in US rivers and lakes (Caraco et al, 1997;Evans et al, 2011) (Hussner, 2012), some with high production and biomass (Hussner, 2009); invasive floating macrophytes such as the water hyacinth (Eichhornia crassipes) have been documented to increase CO 2 and CH 4 levels in tropical rivers (Koné et al, 2009(Koné et al, , 2010, but this remains undocumented in temperate rivers.…”
Section: Introductionmentioning
confidence: 99%
“…Froman environmental management perspective, aquatic plant invaders (APIs) are a growing concern, because they constitute 11% (4 of 36) of the world's most invasive plant species; additionally, they pose a threat to biodiversity, ecosystem balance, and water bodies (Hussner, 2012;Leppä-koski et al, 2013;Svirčev et al, 2014;Luque et al, 2014). The environmental niche describes the response of APIs to the distribution of suitable habitats.…”
Section: Introductionmentioning
confidence: 99%
“…The expansion and evolution of APIs in non-native ranges, and their propagation along barriers may instill an environmental niche shift. Previous studies have also shown that environmental niche shift is related to human influence (Riis et al, 2012;Hussner, 2012;Donoghue and Edwards, 2014;Svirčev et al, 2014;Nunes et al, 2015). API seedlings have been imported to non-native regions for ecological restoration, agricultural production, or even as ornamental plants (De Groot et al, 2002;Leppäkoski et al, 2013;Riis et al, 2012;Kaufman and Kaufman, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Sarika 2005, DAISIE 2008, Zenetos et al 2009, Arianoutsou et al 2010, Hussner 2012, Dimopoulos et al 2013. Zenetos et al (2009) in their literature review about alien aquatic species in Greece, remark that "the alien freshwater flora of Greece is poorly studied, since several regions and habitats likely to host such species are under-sampled.…”
Section: Discussionmentioning
confidence: 99%